PENYUSUNAN LAPORAN KEUANGAN MENGGUNAKAN ACCURATE ONLINE PADA PONDOK BAKSO MAS ARUL - Pranita, Fera Lufhidarani; Adelia, Elsa; Janaka, Janaka (POLITEKNIK LP3I JAKARTA, 2023)
Financial reports have an important role in helping and monitoring the financial condition of various parties to the financial performance of a business, including micro businesses such as Pondok Bakso. This study aims to compile financial reports at Pondok Bakso Mas Arul for the March 2025 period which utilizes Accurate Online as the main tool. The method used is a qualitative descriptive method which includes collecting daily transaction data and compiling financial reports along with profit and loss statements, balance sheets and cash flows. The results of this study indicate that the use of Accurate Online can increase efficiency and accuracy in compiling financial reports so that business owners can monitor financial conditions in real time. Thus, the use of Accurate Online can be a practical and economical solution for small business actors in managing their finances independently and professionally.